Study on Bacterial Strain UL188 Isolated from Fermented Meat of Phu Tho Province in Vietnam - Ha, Hoang Thu; Hue, Luu Thi Thanh; Quyen, Nguyen Huynh Minh; Loi, Nguyen Van; Huy, Nguyen Quang; Uyen, Nguyen Quynh (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Lactic acid bacteria (LAB) and bacteriocins are of great interest to scientists due to their valuable properties. Therefore, LAB and bacteriocins have been applied in many fields such as food industry, pharmacy and medicine. In this study, one LAB strain, isolated from the fermented meat of Phu Tho province,Vietnam was studied. Some primary characteristics of the LAB strain, including morphology and classification as well as the bacteriocins synthesized by this strain were investigated. In particular, the bacteriocins were primarily evaluated for their activity unit (AU) and the effects of temperature and pH on the activities were examined as well. In addition, the bacteriocins were primarily purified by using ion exchange chromatography. Keywords : Lactic acid bacteria (LAB), bacteriocins, activity unit (AU), chromatography.